Blister formation and hydrogen retention in aluminium and beryllium: A modeling and experimental approach. (August 2017) - Quirós, C.; Mougenot, J.; Lombardi, G.; Redolfi, M.; Brinza, O.; Charles, Y.; Michau, A.; Hassouni, K.
Highlights: Aluminum was exposed to hydrogen plasma. Blisters start to form at the grain boundaries and their density increases linearly with time. Hydrogen retention and bubble formation was simulated for beryllium and aluminum. Beryllium and aluminum have different hydrogen retention and bubble formation mechanisms. Abstract: Experiments were performed in a low pressure-high density plasma reactor in order to study the impact of hydrogen retention in aluminium under plasma conditions. Microscopy scans of the surface were performed before and after 1 h plasma exposure (fluence 6.1 × 10 23 ions/m 2 ) where it is seen that blisters start to nucleate at the grain boundaries. Investigation on blister growth kinetics was performed for fluences ranging between 6 × 10 23 and 3.7 × 10 24 ions/m 2 . The evolution of the characteristic size of the projected area was also analyzed. Finally, a macroscopic rate equations (MRE) code was used to simulate hydrogen retention and diffusion in Al and bubble growth in the bulk was simulated using experimental results. This model was also used to simulate these phenomena in Be and compare its behavior with respect to Al.